2020
DOI: 10.1037/cdp0000319
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in general physical symptoms and medically unexplained physical symptoms: Investigating the role of education.

Abstract: Objectives: Distressing physical symptoms (e.g., back pain, nausea), many of which lack medical explanation, are a common cause for medical help seeking. However, racial/ethnic and educational differences may complicate identification and explanation of such symptoms, potentially contributing to clinician misdiagnosis and patient dissatisfaction. To better understand this issue, we examined racial/ethnic differences in general physical symptoms (GPS) and, more specifically, medically unexplained physical sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
1
10
0
2
Order By: Relevance
“…In general practice, it is normal to encounter patients with no medical explanation for their symptoms and no medical diagnosis. According to the literature, incidences of this phenomenon range from 10 to 50%, with significantly higher incidences in specialty clinical settings [ 1 - 3 ]. A cross-sectional design has most often been employed in investigations involving patients with medically unexplained physical symptoms (MUPS).…”
Section: Introductionmentioning
confidence: 99%
“…In general practice, it is normal to encounter patients with no medical explanation for their symptoms and no medical diagnosis. According to the literature, incidences of this phenomenon range from 10 to 50%, with significantly higher incidences in specialty clinical settings [ 1 - 3 ]. A cross-sectional design has most often been employed in investigations involving patients with medically unexplained physical symptoms (MUPS).…”
Section: Introductionmentioning
confidence: 99%
“…As with all ideographic research, generalisability is theoretical (i.e. to allow consideration of resonances with other families living with PPS), and differences – such as cultural and socio-economic contexts – should be explored in future research ( Evangelidou et al, 2020 ). Similarly, alternative family structures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that female patients' common somatic symptoms remain more often medically unexplained than male patients' somatic symptoms. 1,2 Yet, only recently it has been shown that the negative association between female sex and medically unexplained symptoms is mediated by the performed diagnostic interventions in primary care. 3 Recent studies show that differences between women and men in primary care diagnostic trajectories for somatic symptoms are not uncommon.…”
Section: Introductionmentioning
confidence: 99%